2001
DOI: 10.1046/j.1471-4159.2001.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity sodium–vitamin C co‐transporters (SVCT) expression in embryonic mouse neurons

Abstract: The sodium±vitamin C co-transporters SVCT1 and SVCT2 transport the reduced form of vitamin C, ascorbic acid. High expression of the SVCT2 has been demonstrated in adult neurons and choroid plexus cells by in situ hybridization. Additionally, embryonic mesencephalic dopaminergic neurons express the SVCT2 transporter. However, there have not been molecular and kinetic analyses addressing the expression of SVCTs in cortical embryonic neurons. In this work, we con®rmed the expression of a SVCT2-like transporter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
115
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 56 publications
16
115
1
2
Order By: Relevance
“…Therefore, SVCTs are the major homeostatic regulators of vitamin C levels in the central nervous system (CNS; Rice, 2000), actively uptaking its reduced form, L-ascorbate (Caprile et al, 2009;Castro et al, 2001;Garcia et al, 2005). L-ascorbate is transported against its concentration gradient ( Daruwala et al, 1999;Tsukaguchi et al, 1999), and thus the energy required for the transport is supplied by sodium exchange through the Na + /K + -ATPase pump (Castro et al, 2001). The relationship between sodium and ascorbate transport was found to be 2:1, and the order of union to the substrate was sodium-ascorbate-sodium (Godoy et al, 2007).…”
Section: Vitamin C Transporters In the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, SVCTs are the major homeostatic regulators of vitamin C levels in the central nervous system (CNS; Rice, 2000), actively uptaking its reduced form, L-ascorbate (Caprile et al, 2009;Castro et al, 2001;Garcia et al, 2005). L-ascorbate is transported against its concentration gradient ( Daruwala et al, 1999;Tsukaguchi et al, 1999), and thus the energy required for the transport is supplied by sodium exchange through the Na + /K + -ATPase pump (Castro et al, 2001). The relationship between sodium and ascorbate transport was found to be 2:1, and the order of union to the substrate was sodium-ascorbate-sodium (Godoy et al, 2007).…”
Section: Vitamin C Transporters In the Brainmentioning
confidence: 99%
“…Each transporter has a distinct distribution. For example, in situ hybridization and immunohistochemical experiments have shown that SVCT2 is expressed mostly in CNS within choroid plexus cells (Garcia et al, 2005;Tsukaguchi et al, 1999), embryonic neurons (Castro et al, 2001), tanycytes (Garcia et al, 2005) and adult cortical and hippocampal neurons (Astuya et al, 2005) (Figure 4A-B). Although most astrocytes do not express SVCT2, our results indicate that astrocytes of the external area of the entorhinal cortex express SVCT2 ( Figure 4C,E).…”
Section: Vitamin C Transporters In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Only reduced vitamin C, ascorbic acid, is present in human plasma and in cells and tissues, and the cellular content of vitamin C can exceed by several orders of magnitude the plasma levels of the vitamin (2). Human cells transport ascorbic acid in a concentrative manner through sodium-ascorbic acid co-transporters (3)(4)(5)(6)(7)(8); they also transport oxidized vitamin C, dehydroascorbic acid, down its concentration gradient through facilitative glucose transporters (9 -18). Although all cells express facilitative glucose transporters, the absolute specificity of these transporters for dehydroascorbic acid is in apparent contradiction to evidence indicating that vitamin C is present in human plasma only as ascorbic acid.…”
mentioning
confidence: 99%
“…The molecular basis of ascorbic acid efflux is not yet well known. Neurons can take up ascorbic acid efficiently because they express SVCT2 (Castro et al, 2001). Ascorbic acid is oxidized within neurons Fig.…”
Section: Metabolic Activation In Astrocytesmentioning
confidence: 99%